Pengaruh Pola Asuh Permisif Terhadap Perkembangan Sosial Emosional Anak Usia Dini di TK Al-Hidayah Kabupaten Bone - Anisya Ramadanty; Putriani Putriani; Hibana Hibana; Na'imah Na'imah; Sovia Mas Ayu (UIR PRESS, 2022)
This study aims to determine whether there is an effect of permissive parenting on the socio-emotional development of early childhood in Kindergarten in Tanete Riattang District, Bone Regency. The research location is in Al-Hidayah Kindergarten. The population in this study were all students and parents of Al-Hidayah Kindergarten students totaling 31 students along with their parents. Group A consists of 15 children, group B consists of 16 children. As for the sample, the researcher took 16 parents and 1 teacher (homeroom teacher). The method used in this research is quantitative research. The sampling technique in this study was carried out using the results of questionnaires and interviews. The data analysis technique used is the Regression Correlation Coefficient formula. The results showed that the results of research conducted through the results of questionnaires and interviews obtained the results of the calculation of the regression correlation coefficient where the value of the regression Y = a + bX = 2.33 + 0.78 . a = 2.33 means that if the influence of parenting has a value of 0 (none) then social emotional development has a value of 2.33. b = 0.78 means that if the permissive parenting is 1, it will affect the emotional social has a value of 0.78. And the coefficient value where the coefficient value is 0.06, it can be seen that there is a relationship or influence of permissive parenting on the socio-emotional development of early childhood.